Effects of Injected Iron and Siderophores on Infections in Normal and Immune Mice - Kochan, Ivan (1978)
The fate of virulent and avirulent strains of Salmonella typhimurium in untreated and iron-injected mice and in transferrin-containing media demonstrated a direct relationship between bacterial virulence and the ability of bacteria to acquire transferrin-bound iron. Effects of injected iron on the development of infections with virulent and avirulent bacterial strains were determined in normal and immune mice by determinations of bacterial numbers in tissue homogenates and the mortality of infected animals. Results showed that infected and iron-injected mice died much more rapidly and frequently from overwhelming infections than infected and saline-injected mice. The infection-promoting effect of iron varied with the degree of bacterial virulence; the more virulent the bacteria, the more helpful was iron for the development of lethal infections. Siderophores promoted lethal infections in mice infected with virulent but not with avirulent bacteria. Experiments with vaccinated animals showed that iron exerted a deleterious effect on acquired immunity. Immune mice infected with virulent bacteria and injected with iron developed lethal infections as rapidly and nearly as frequently as similarly treated normal mice. Siderophores did not promote the development of lethal infections in immune mice. The effectiveness of iron, but not of siderophores, to promote bacterial infections in vaccinated mice revealed that acquired immunity is dependent upon the activity of an iron-neutralizable antibacterial system.